Ecological Politics : For Survival and Democracy. - Rensenbrink, John (Lexington Books, 2016)
Politics stoutly resists efforts to meet dire threats to human survival, such as climate change, industrial poisons, and "natural" disasters. This book seizes on new discoveries of nature's interconnective ways to demand politics and government without violence, fair and equal access to the ballot box, dialogue across differences, and electoral action from the ground up by an independent political party.